2013
DOI: 10.1093/jrr/rrt112
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of cochlear dose reduction by proton beam therapy for medulloblastoma in childhood

Abstract: Background: The aim of this study is to evaluate the cost-effectiveness of proton beam therapy with cochlear dose reduction compared with conventional X-ray radiotherapy for medulloblastoma in childhood. Methods: We developed a Markov model to describe health states of 6-year-old children with medulloblastoma after treatment with proton or X-ray radiotherapy. The risks of hearing loss were calculated on cochlear dose for each treatment. Three types of health-related quality of life (HRQOL) of EQ-5D, HUI3 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…In PBT, the tumor control rate is similar to that in photon radiotherapy [9][10][11][12][13][14][15][16][17][18][19][20], but late toxicity and the secondary cancer risk should be much lower due to the dose distribution [21]. For this reason, PBT has potential as a treatment for pediatric tumors, but fewer institutions have proton beam centers compared to those with normal photon radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In PBT, the tumor control rate is similar to that in photon radiotherapy [9][10][11][12][13][14][15][16][17][18][19][20], but late toxicity and the secondary cancer risk should be much lower due to the dose distribution [21]. For this reason, PBT has potential as a treatment for pediatric tumors, but fewer institutions have proton beam centers compared to those with normal photon radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in QOL and late effects with proton therapy may be more cost-effective than photon therapy in pediatric patients who are expected to be cured of their disease, particularly when the management of potential second malignancies and late toxicities are evaluated [48]. In a Monte Carlo simulation model of survivors of pediatric medulloblastoma treated at 5 years of age with proton and photon therapy, LAR was estimated from previous studies, and model-valued health effects and costs were estimated per the US Panel on Cost Effectiveness in Health and Medicine.…”
Section: • • the Economics Of Proton Therapymentioning
confidence: 99%
“…All radiotherapy requires expensive equipment and highly qualified staff, but in itself, it is not an expensive treatment and consumes only about 5% of a running oncology budget [2]. A Swiss study has found that the cost of proton radiotherapy is 2.4 times higher than IMRT [48].…”
mentioning
confidence: 99%
“…It can be expected that over time, this can be reduced to 2.1 or even 1.7 times, however proton radiotherapy will probably always remain more expensive that photon therapy [48]. There are two vital economic measures used for analysing the efficiency of medical procedure outcomes: the cost of obtaining an extra 'Quality-Adjusted Life Year' (QALY) or an extra 'Life Year Gained' (LYG).…”
mentioning
confidence: 99%